Comparative Study of HbA1c level measurement by Turbidimetric Inhibition Immunoassay and Boronate Affinity HPLC at Vajira Hospital - Treewatchareekorn, Mala; Chaloeysup, Sirirat (Vajira Medical Journal : Journal of Urban Medicine, 2017)
Objective: This study aimed to compare 2 methods of HbA1c measurement, turbidimetric inhibition immunoassay (TINIA) from Cobas Integra 800 analyzer and boronate affinity HPLC (BA-HPLC) from Premier Hb 9210 analyzer, and analyzed for statistical correlation. Methods: This is a prospective study that measured HbA1c level at Faculty of Medicine Vajira Hospital during December 1-30, 2015. EDTA blood samples were measured for HbA1c by TINIA and BA-HPLC. The data from the two methods were divided into three groups according to HbA1c level: HbA1c 4.0-6.5%, 6.6-8.0% and > 8.0%. HbA1c levels from the two methods were compared and analyzed for statistical correlation. Results: Most of HbA1c levels (73.5%) from 543 specimens measured by BA-HPLC were higher than TINIA. The correlation study of the three groups of HbA1c levels between TINIA and BA-HPLC by using Interclass correlation coefficient (ICC) were 0.872, 0.872 and 0.963 respectively. HbA1c levels from the two methods were well correlated. The bias of the three groups and total group of HbA1c between TINIA and Premier BA-HPLC in + 1.96 SD by Bland-Altman plot were -0.54% to 0.35%, -0.71% to 0.22%, -1.54% to 0.40% and -0.92% to 0.45%, respectively. HbA1c levels from samples with abnormal hemoglobin (HbCS and HbF) had more difference between two methods than the others. Conclusion: All the three groups of HbA1c measured by TINIA and BA-HPLC were well correlated. Most of HbA1c levels from TINIA were higher than BA-HPLC, especially with HbA1c >8.0%. Measurement of HbA1c by the two methods might be different in patients with abnormal hemoglobin. Laboratories should not use analyzers with different methods for substitution or reporting HbA1c levels together .